Promotional approaches to undergraduate recruitment for marginalised courses and marginalised students - Frost, Helen (2017)
This research challenges the norms of undergraduate recruitment promotion practice responding to political, economic, social and technological drivers in a competitive environment. The practical problem is defined from a marketing practitioner standpoint working with core approaches which do not represent nuanced subject and audience needs, instead leaving them on the margins of the institutional recruitment offer. Marginalised students are represented by those who did not attend private or high-achieving state schools, including, but not restricted to, those identified by widening participation policy. Marginalised subjects are represented by selected arts and humanities courses without overt links to specific professions. These aspects of marginalisation triangulated from an elite institution perspective create a framework for investigating the problems created by core promotional practice, and for developing solutions. The use of a case study supported by design-based research methods allows for practical research outputs in a live environment. Mixed methods are employed to gather data from a small sample of insider sources (nine students and seven tutors) and general public sources (1,923 online reader responses to 31 news articles and forum posts). The insider and public accounts provide an alternative marketing intelligence corpus to normative large-scale quantitative data. This is used to inform design principles incorporated into a prototype package of three promotional resources and a sustainable strategy. The success of the challenge to promotional practice norms materialises not simply through public-facing practical solutions as initially anticipated, but also though the collaborative processes of the enquiry, improving professional relations between marketing administrative and academic staff. The alternative approaches realised through this research can be summarised as a move towards small-scale market intelligence gathering and resource production to meet the nuanced needs of marginalised subjects and audiences, and an alteration to professional practice which acknowledges academics as marketing partners. These outputs are now employed within routine practice within the boundaries of the original study, and have the potential to be generalisable through wider discussions among HE marketing practitioners.